Pengaruh Social Influence, Literasi Keuangan, dan Self Control Terhadap Perilaku Menabung Mahasiswa - Safitri, Dyah Ayu; Rafsanjani, Mohamad Arief (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The low level of saving behavior among students is an issue that needs to be studied in depth because it can have a major impact on their ability to manage finances and maintain financial stability in the future. The purpose of this study is to analyze the influence of social influence, financial literacy, and self-control on the saving behavior of Economics Education students at Surabaya State University. This study applies a quantitative approach with a convenience sampling method. There were 121 students who participated in this study. Data collection was carried out by distributing questionnaires designed based on indicators for each variable and then analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results show that social influence has a positive and significant effect on financial literacy and self-control. Financial literacy and self-control affect saving behavior. Financial literacy mediates the effect of social influence on saving behavior. However, social influence does not have a significant effect on saving behavior, either directly or indirectly through self-control. Based on the above findings, it can be seen that student saving behavior is more influenced by internal factors, such as financial literacy and self-control, than by social environmental influences. These findings also explain the important role of social influence in shaping students' financial literacy and self-control.